Defining normal pouch function in patients with ileal pouch‐anal anastomosis: a pilot study. Issue 12 (11th March 2022) - Quinn, Kevin P.; Busciglio, Irene A.; Burton, Duane D.; Inoue, Akitoshi; Lee, Yong S.; Heiken, Jay P.; Sheedy, Shannon P.; Fletcher, Joel G.; Raffals, Laura E.
Summary: Background: Most patients experience good functional outcomes following ileal pouch‐anal anastomosis (IPAA) for ulcerative colitis. Aim: We aimed to determine if asymptomatic patients with an IPAA had findings consistent with normal defecation on standard objective anorectal tests. Methods: Patients 18–65 years old with IPAA and self‐reported healthy pouch function were recruited. Patients with chronic pouchitis, Crohn's disease, anastomotic stricture, or indication for IPAA other than ulcerative or indeterminate colitis were excluded. Patients underwent an interview with an abbreviated Rome Questionnaire followed by high‐resolution ano‐pouch manometry, balloon expulsion test, pouch barostat, and magnetic resonance (MR) defecography. Results: Twenty patients completed all testing. Six patients were excluded from the final analysis due to symptoms suggestive of pouch evacuation disorder on the abbreviated Rome Questionnaire ( n  = 2), structural abnormality on MR imaging ( n  = 3), or both ( n  = 1). Of the remaining 14 patients, mean anal resting pressure during high‐resolution manometry was 72 ± 16 mmHg, mean anal squeeze pressure was 247 ± 69 mmHg, and mean pouch‐anal gradient during the simulated evacuation was −27 ± 37 mmHg. The meantime to balloon expulsion was 54 seconds. During dynamic MR defecography, the mean descent of ano‐pouch junction was 2.6 cm, and mean pouch evacuation was 44.5% and 74.2% pre‐ and posttoilet phase, respectively. Conclusions: A substantial proportion of patients with IPAA and self‐reported healthy pouch function have anatomic and/or functional abnormalities of the pouch. In asymptomatic IPAA patients with an anatomically normal pouch, we have proposed normal parameters for high‐resolution ano‐pouch manometry, time to balloon expulsion, pouch barostat, and MR defecography. Abstract : Anatomic axial T2‐weighted MR images without (A) and with (B) fat saturation in an asymptomatic patient with IPAA show an intersphincteric perianal fistula (arrow) with internal opening below the level of the anastomosis.